Diagnosis and Differential Diagnosis of Neurological Adverse Events during Immune Checkpoint Inhibitor Therapy. (7th December 2020) - Möhn, Nora; Mahjoub, Susann; Gutzmer, Ralf; Satzger, Imke; Beutel, Gernot; Ivanyi, Philipp; Golpon, Heiko; Wattjes, Mike P.; Stangel, Martin; Skripuletz, Thomas
Abstract : Therapy with immune checkpoint inhibitors (ICIs) has improved overall survival and cancer-related morbidity of cancer treatment even in cancer entities with poor prognosis. Since the approval of the first ICI, ipilimumab, for treatment of advanced melanoma by the Food and Drug Administration (FDA) in 2011, the spectrum of indications and approved ICIs has grown, rapidly. Up to now, seven different ICIs for more than 20 indications are available. However, their mechanisms of action can lead to immune-related adverse events (irAEs). In particular, neurological irAEs are clinically relevant. Although they are rare, an early and accurate diagnosis is challenging and neurological disease course and sequelae are potentially fatal. Between 08/2017 and 03/2020, 31 patients received ICI treatment at Hannover Medical School and presented with neurological adverse events (N-irAEs). Treated malignancies were metastatic melanoma, bronchial carcinoma, and urothelial cell carcinoma. All patients received comprehensive neurological diagnostics including clinical examination and magnetic resonance imaging (MRI). Cerebrospinal fluid (CSF) analysis was obtained in 21 patients and electroneurography was performed in 22 patients. Although N-irAEs were suspected in all 31 patients, 11 patients had other conditions leading to neurological symptoms including tumor metastases in seven patients and hemorrhagic or ischemic stroke in four patients. In the following, these patients are referred to as the differential diagnosis (DD) group. Patients with N-irAEs suffered from immune mediated neuropathy (9/20), myositis and/or myasthenic syndrome (6/20), or encephalitis/cerebellitis (5/20). Except for cell count, CSF results did not differ between the N-irAEs and the DD group. Symptoms related to N-irAEs are rather unspecific potentially mimicking other tumor-related symptoms such as metastases. Patients with malignancy are predominantly not treated by neurologists. Because of the complexity of neurological symptoms, detailed neurological investigations in specialized institutions are necessary in patients with new neurological symptoms and need to be critically discussed with treating oncologists.